2018
DOI: 10.1002/adma.201705221
|View full text |Cite
|
Sign up to set email alerts
|

IR‐Driven Ultrafast Transfer of Plasmonic Hot Electrons in Nonmetallic Branched Heterostructures for Enhanced H2 Generation

Abstract: The ultrafast transfer of plasmon-induced hot electrons is considered an effective kinetics process to enhance the photoconversion efficiencies of semiconductors through strong localized surface plasmon resonance (LSPR) of plasmonic nanostructures. Although this classical sensitization approach is widely used in noble-metal-semiconductor systems, it remains unclear in nonmetallic plasmonic heterostructures. Here, by combining ultrafast transient absorption spectroscopy with theoretical simulations, IR-driven t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 61 publications
0
90
0
Order By: Relevance
“…If photocatalysts are to be used to decompose water, their energy band gap (Eg) must be greater than 1.23 eV (<1,000 nm) and less than 3.0 eV (>400 nm) to respond in the visible region (Pihosh et al, 2015). In other words, the semiconductor photocatalyst must have a relatively small band gap (1.23 eV < E g < 3.0 eV) to absorb as much light as possible for the purpose of photogenerated electrons/holes (Zhang et al, 2018). The results of hydrogen production by photolysis showed that the hydrogen production efficiency of g-C 3 N 4 improved considerably after WO 2.72 was incorporated.…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…If photocatalysts are to be used to decompose water, their energy band gap (Eg) must be greater than 1.23 eV (<1,000 nm) and less than 3.0 eV (>400 nm) to respond in the visible region (Pihosh et al, 2015). In other words, the semiconductor photocatalyst must have a relatively small band gap (1.23 eV < E g < 3.0 eV) to absorb as much light as possible for the purpose of photogenerated electrons/holes (Zhang et al, 2018). The results of hydrogen production by photolysis showed that the hydrogen production efficiency of g-C 3 N 4 improved considerably after WO 2.72 was incorporated.…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…Sulfides such as MoS 2 or In 2 S 3 have been used in this context [ 106 , 107 ]. Regarding oxides, we can highlight the cases of Ag 2 O [ 108 ], and WO x [ 109 , 110 ]. These systems and particularly the latter are real, full-spectrum catalysts, with utilization of the UV-visible-nearIR electromagnetic range.…”
Section: Composite Photocatalystsmentioning
confidence: 99%
“…This appears as a mixture of thermal and light effects due to the non-radiative and radiative de-excitation taking place under visible and IR illumination conditions. The effect is not a simple sum and a clear synergy comes out from the analysis of Figure 7 [ 110 ]. Such a behavior was also present in Ru-RuO x core-shell structures supported in anatase TiO 2 [ 112 ].…”
Section: Composite Photocatalystsmentioning
confidence: 99%
“…It seems that the CB and VB of ZnS are both more negative than those of SnS 2 , the photo‐induced electrons at the CB of ZnS will transfer into the CB of SnS 2 while the photo‐induced holes at the VB of SnS 2 will transfer into the VB of ZnS. In this way, the photo‐produced carriers will flow into different semiconductors and the carriers’ migration efficiency is enhanced . The enhancement of carriers’ migration efficiency can be confirmed by the EIS and FL results (Figure ).…”
Section: Resultsmentioning
confidence: 56%